Prevalence and determinants of asthenopia among ophthalmologists in China: a national cross-sectional survey - Lin, Na; Zhu, Yu; Wu, Xiaotian; Yang, Maoyuan; Lu, Fan; Deng, Ruzhi (Frontiers in Public Health, 2023)
Introduction The role of ophthalmologists is defined by tasks requiring visual effort, emphasizing the importance of examining their condition within the realm of occupational visual health. Our goal was to explore the occurrence of asthenopia among Chinese ophthalmologists and identify contributing factors through the use of a reliable and validated survey instrument. Methods A national cross-sectional online survey was carried out in June 2017, involving 6,220 practicing ophthalmologists in China. Utilizing an 11-item Asthenopia Survey Questionnaire with established reliability and validity. Prevalence rates of asthenopia among subgroups categorized by age, gender, hospital classification, physician level, daily near vision activity duration, sleep duration, sleep quality, presbyopia status, and history of eye surgery were determined using the independent t-test, chi-square test and bonferroni test. Multiple logistic regression analysis was employed to pinpoint independent factors linked to asthenopia. Results Out of the 5,009 ophthalmologists who completed the survey, a 40.7% prevalence of asthenopia was identified. Multivariate analysis revealed that good sleep quality (OR: 0.24, 95%CI: 0.20–0.30), moderate sleep quality (OR: 0.47, 95%CI: 0.38–0.59), engaging in daily near vision activities for less than 7 h (OR: 0.76, 95%CI: 0.68–0.86), having daily sleep duration exceeding 7 h (OR: 0.87, 95%CI: 0.77–0.98), and working in tertiary hospitals (OR: 0.88, 95%CI: 0.78–0.99) were protective factors against asthenopia. Conversely, presbyopia was identified as a risk factor (OR: 1.33, 95%CI: 1.04–1.70). All calculated p values were below 0.05. Age, gender, physician level, and eye surgery history were not related factors. Conclusion Asthenopia is prevalent among Chinese ophthalmologists, with employment in tertiary hospitals providing a protective effect and presbyopia is a risk factor. Preventive strategies include improving sleep quality, restricting daily near vision activity to under 7 h, and extending daily sleep duration to over 7 h. Further investigation is needed to explore the protective implications of working in tertiary hospitals.